Clinical laboratory registration system using contactless card - Noor Fatimah, Mazlan (2009)
In accordance with the advancement in technology,most companies or organizations have also been improving in the way they store data or important details belonging towards the organization more secure and not easy being intruded by people who are not rJatd.By using the smart card is one way to ensure that data or important details that are just more secure and accessible only by those responsible.In this way,the probability of data to be accessed by people who do not respect is thinner.Smart card can be applying in few applications such as financial,identification, and also in health care.Smart health cards can improve the security and privacy of patient information,provide the secure carrier for portable medical records,reduce health care fraud, support new processes for portable medical records, provide secure access to emergency medical information, enable compliance with government initiatives and mandates, and provide the platform to implement other applications as needed by the health care organization. Clinical Laboratory Registration System is a prototype that allows patients' registration by using contactless smart card.The patients' data will retrieve from smart card,and the registration will do by clerk. After the patients' had done the clinical test, all the test result will save in CLRS's database.CLRS is developed to overcome problems since the process of patients' registration is still done manually.Besides,the test result of clinical test also saved manually in the log book.The problems that may arise during the registration are improperly filled the form and it will consume times to record the test results in the database.Besides,the test results become more secure because only the doctor and lab staff can view the clinical result.